1, 2, 4-triazole-5(4H)-one based novel peripherally tetrasubstituted metal-free and metallophthalocyanines: Synthesis, characterization, and electrochemical and spectroelectrochemical properties. Issue 6 (3rd June 2017) - Aktaş, Ayşe; Ünlüer, Dilek; Kobak, Rabia Zeynep Uslu; Acar, İrfan and Düğdü, Esra and Koca, Atıf and Kantekin, Halit
ABSTRACT: In this study, the synthesis of metal-free and metallophthalocyanines containing four 4-[2-(4-methoxyphenyl)ethyl]-5-methyl-2, 4-dihydro-3H-1, 2, 4-triazol-3-one substituents at the peripheral positions were reported. The structures of compounds were characterized using IR, 1 H NMR, 13 C NMR, mass spectroscopies, and UV-Vis. Electrochemistry of the complexes were studied with voltammetric and in situ spectroelectrochemical measurements in different electrolytic systems. MPcs having redox inactive metal centers (H +, Zn +2, Cu +2, and Ni +2 ) just illustrated similar Pc-based electron transfer reactions. Due to the different effective nuclear charge of the ions in the core of Pc ring, small potential shifts and reversibility differences were observed between the redox processes of these complexes. MPcs having redox-active metal centers (Co +2 and TiO +2 ) gave metal-based electron transfers in addition to Pc-based processes. Electrolyte type of the measurement system significantly influenced oxidation behaviors of CoPc due to the coordination of polar coordinating solvent molecules to the oxidized Co III center of CoPc. Spectra and color of the electrogenerated MPc species were determined with in situ spectroelectrochemical measurements.